Dualism of Tiktok’s Algorithmic Impact: Disruption of Students’ Sexual Identity in Islamic Education at Palangkaraya Universities - Nuraliah Ali; Mulida Hayati; Abdul Ziqron Mopoliu (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Over 62% of Muslim college students report encountering LGBTQ+ content on TikTok-how does Islamic education respond to this digital exposure?. This study explores the dual impact of TikTok’s algorithm and its usage intensity on the formation of sexual identity and orientation among Muslim students at State General Universities (PTUN) in Central Kalimantan. This study used a mixed-method approach with a Concurrent Embedded design, in which combined quantitative regression analysis of Likert-scale questionnaire data (N = 312) and qualitative thematic analysis from in-depth interviews and literature reviews. The sample was determined using stratified random sampling based on students' semester levels. The study results TikTok significantly influences students' sexual identity and orientation (r = 0.583, p < 0.01), while Islamic education has a more modest effect (r = 0.299, p < 0.01). Together, both variables explain 46% of the variation (RÂ² = 0.460). Notably, 70% of respondents reported experiencing value conflict after being exposed to sexual content. Regression results indicate that TikTok and Islamic education together explain 46% of the variance (RÂ² = 0.460) in students’ sexual identity orientation. No significant link was found between TikTok usage and internalization of Islamic values (r = -0.079, p = 0.214), suggesting parallel but disconnected development paths. These findings call for urgent integration of digital Islamic literacy to Islamic education curriculum to mitigate the effect of TikTok’s algorithm, and use of social media da’wah within Islamic education frameworks to confront algorithmic influences effectively.